2018
DOI: 10.1016/j.jaci.2017.08.024
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the atopic march: Results from the Canadian Healthy Infant Longitudinal Development Study

Abstract: Atopic dermatitis without concomitant allergic sensitization was not associated with an increased risk of asthma. In combination, atopic dermatitis and allergic sensitization had strong interactive effects on both asthma and food allergy risk at age 3 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
120
0
6

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 150 publications
(148 citation statements)
references
References 37 publications
8
120
0
6
Order By: Relevance
“…However, we and others have noted that "atopic dermatitis" is often a misnomer as quite frequently AD is diagnosed in the absence of allergic sensitization. In another publication from this population-based, longitudinal birth cohort, we reported that AD without evidence of allergic sensitization was not associated with an increased risk of subsequent asthma, 35 whereas the combination of AD and allergic sensitization at age 1 year was associated with increased risks for both asthma and food allergy at 3 years. The combined effect of diagnosed AD and allergic sensitization was greater than the sum of their individual effects on these risks.…”
Section: Discussionmentioning
confidence: 76%
“…However, we and others have noted that "atopic dermatitis" is often a misnomer as quite frequently AD is diagnosed in the absence of allergic sensitization. In another publication from this population-based, longitudinal birth cohort, we reported that AD without evidence of allergic sensitization was not associated with an increased risk of subsequent asthma, 35 whereas the combination of AD and allergic sensitization at age 1 year was associated with increased risks for both asthma and food allergy at 3 years. The combined effect of diagnosed AD and allergic sensitization was greater than the sum of their individual effects on these risks.…”
Section: Discussionmentioning
confidence: 76%
“…We have previously reported that the clinical assessment of AD using the UK Working party criteria provided the strongest correlation with clinical outcomes of allergic diseases at 3 years. 14 We have now extended follow-up time, and evaluated which AD diagnostic measure was most associated with clinical outcomes (atopy, asthma, allergic rhinitis, and food allergy) at age 5 years. We applied unadjusted Poisson regression models to calculate the risk ratios of exhibiting these characteristics associated with AD diagnosed by each method.…”
Section: Discussionmentioning
confidence: 99%
“…1 Other studies have utilised electronic medical records 7,8 seeking a diagnosis by an attending physician, while others relied on parentreported physician diagnosis, where parents were typically asked "Has your child been diagnosed with eczema?". [9][10][11][12] Some studies have employed direct examination of the child by a health care professional, [13][14][15][16] while others have combined more than one of these methods. 13,15 It is unknown if these methods are comparable.…”
Section: Introductionmentioning
confidence: 99%
“…In many children with asthma, the appearance of different allergic conditions follows a sequence that has been labelled the “atopic march” [76]. This sequence connects the different expressions of allergic diseases that vary with age, which often have transient symptoms.…”
Section: Reviewmentioning
confidence: 99%